High temperature flash pyrolysis characteristics of waste plastics (SRF) in a bubbling fluidized bed: Effect of temperature and pelletizing. (15th October 2022) - Tokmurzin, Diyar; Nam, Ji Young; Lee, Tae Ryeon; Park, Sung Jin; Nam, Hyungseok; Yoon, Sang Jun; Mun, Tae-Young; Yoon, Sung Min; Moon, Ji Hong; Lee, Jae Goo; Lee, Dong Hyun; Ra, Ho Won; et al.
Highlights: SRF high temperature flash pyrolysis in BFB favors gas yield with high LHV. C1 -C3 gases reach 0.391 g/gfuel and H2 reaches 22.42 vol% at 900 °C. Tar olefins and paraffins are cracked at 800–900 °C yielding more C1 -C3 hydrocarbons. Tar at 800–900 °C mostly consists of aromatics originating from PET, PS, and biomass. At 600 °C tar is the major product with paraffins and olefins as main constituents. Abstract: Utilization of municipal solid waste (MSW) non-recyclable combustible fractions abundant in mixed plastics such as solid recovered fuel (SRF) is becoming increasingly widespread due to its sustainability. This study investigates utilization of pelletized mixed plastic SRF using fluidized bed (FB) flash pyrolysis at high temperature, unlike previous studies that focused on low temperature pyrolysis. The effect of temperature on the pyrolysis of SRF was investigated using an externally heated bubbling fluidized bed (BFB) reactor having an internal diameter of 0.114 m and a height of 1 m. Experiments were conducted with an inert fluidizing agent (N2 ) in the temperature range of 600–900 °C. The pyrolysis products such as gas, char, and tar were analyzed, and the mass balance was determined. High temperature flash pyrolysis favors production of high LHV product gas unlike previous studies which were mostly focusing on liquids production. The gas yield increases from 0.285 g/gfuel to 0.680 g/gfuel with increasing temperature from 600 °C to 900 °C. GC–MS analysis of the tar revealed that increasing the temperature intensifies the cracking of naphthenes, alcohols, and olefins, and increases the relative percentage of aromatic hydrocarbons up to 85.1 % at 900 °C. When fluffy SRF was pyrolyzed, gas yield was slightly higher than the pelletized SRF at 800 °C suggesting that low temperature gradient increases gas yield and decreases char yield. Fluffy SRF pyrolysis tar also mainly consists of aromatics and esters. The process produces high calorific gas and reveals the reaction mechanisms relevant to gasification processes.